Diagnostic Accuracy of Prostatic Specific Antigen Densityin Different Prostatic Disorders - Bashir, Qamar; Haroon, Zujaja Hina; Asif, Naveed; Haroon, Azka; Asif, Muhammad; Jaffar, Syed Raza (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the diagnostic accuracy of PSA density in Prostate Cancer, Benign Prostatic Hyperplasia (BPH) and Prostatitis, taking biopsy as the gold standard. Study Design: Cross-sectional study. Place and Duration of Study: Chemical Pathology and Endocrinology Department, Armed Forces Institute of Pathology (AFIP) in collaboration with Histopathology department, AFIP, Armed Forces Institute of Urology (AFIU) and Institute of Radiology (AFIRI) Rawalpindi Pakistan from Mar 2019 to Mar 2020. Methodology: Prostate-specific antigen was analyzed on a fully automated random-access immunoassay-ADVIA® Centaur XP. Prostate volume was measured through transrectal imaging technique, and prostate density was obtained by dividing total Prostate-specific antigen by prostate volume. Specificity and sensitivity, along with the positive predictive and negative predictive value of both Prostate-specific antigen and Prostate-specific antigen density (PSAD), were calculated. In addition, the Receiver Operating Characteristic (ROC) curve was plotted for total Prostate-specific antigen and Prostate-specific antigen density PSA separately. Results: Overall, 129 subjects were registered in the study. Out of these 129 individuals, 59 (45.7%) had prostate cancer, 52 (40.3 %) were benign prostatic hyperplasia (BPH), and 14% of subjects had other prostatic disorders. Total Prostate-specific antigen (PSA) had a sensitivity of 75.61% with a specificity of 76% while Prostate-specific antigen density showed 88% sensitivity and 86% specificity. The area under the curve (AUC) for total Prostate-specific antigen was 0.66, while that for total Prostate-specific antigen density (PSAD) was 0.87. Conclusion: Prostate-specific antigen density is a better predictive and non-invasive diagnostic marker for different prostatic disorders than total Prostate-specific antigen. It has.......